2018
DOI: 10.1111/liv.13877
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disorders across hepatocellular carcinoma in Italy

Abstract: Our "real world" study suggests that metabolic disorders shape the clinical presentation of HCC but do not seem to play a major role in setting patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 44 publications
1
14
2
Order By: Relevance
“…The strong statistical power allowed by our large sample size may explain that we could report an independent association between tobacco consumption and mortality after HCC diagnosis, even if the effect size is small (mean survival reduced by 1.6 months) and only opens modest perspectives for secondary prevention. We did not observe an independent association between diabetes and the evolution of HCC, in line with previous evidence [9]. However, we observed a significant, though modest, better prognostic among patients with baseline hypertension (mean survival improved by 1.5 months), contradicting the results observed European patients [9].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The strong statistical power allowed by our large sample size may explain that we could report an independent association between tobacco consumption and mortality after HCC diagnosis, even if the effect size is small (mean survival reduced by 1.6 months) and only opens modest perspectives for secondary prevention. We did not observe an independent association between diabetes and the evolution of HCC, in line with previous evidence [9]. However, we observed a significant, though modest, better prognostic among patients with baseline hypertension (mean survival improved by 1.5 months), contradicting the results observed European patients [9].…”
Section: Discussionsupporting
confidence: 83%
“…HCC etiology may also affect response to treatment and survival [8]. Other conditions, such as metabolic disorders, may affect HCC incidence, but their influence on survival is not clearly established [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the United States, Canada, Australia, New Zealand, and much of Europe, and also the Philippines and Guatemala, have shown increases in cases of HCV and alcohol-related HCC of 42% and 56%, respectively [1,3,[14][15][16][17][18][19][20][21][22]. In western countries, there is an increasing incidence of post-NASH HCC [11,12,[22][23][24]. e use of direct antivirals (DAAs) may also affect HCC epidemiology in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many studies have shown a strong correlation between metabolic comorbidities [type 2 diabetes mellitus, high body mass index (BMI) and concomitant presence of steatosis] and HCC risk. The presence of these comorbidities has been associated with both increased risk of HCC development and cancer related mortality (12,13). For these reasons, European guidelines recommend that patients with cofactors for liver diseases, regardless fibrotic degree, should continue surveillance for HCC, even after HCV eradication (1).…”
mentioning
confidence: 99%